Women’s empowerment through education, resilience, and gender roles in Anne of Green Gables by L.M. Montgomery - Eva Catur Herawati; Rini Susanti Wulandari (Universitas Negeri Semarang, 2025)
This study explores the theme of women’s empowerment in Anne of Green Gables by L.M. Montgomery through the lenses of education, resilience, and gender roles using a liberal feminism. The analysis focuses on how the protagonist, Anne Shirley, navigates a patriarchal society and asserts her agency through academic ambition, personal strength, and the rejection of traditional gender expectations. The study also examines the influence of supporting characters, such as Marilla Cuthbert, Diana Barry, Miss Stacy and Gilbert Blythe in shaping and reflecting changing gender norms. By analyzing the dialogues in the novel, this research demonstrates that education and resilience not only foster Anne’s and the others character personal growth and independence but also challenge societal norms and promote gender equality. The study concludes that literature, as seen in Montgomery’s work, can be a powerful tool for feminist critique and social transformation.